STUDI PENENTUAN NILAI RESISTOR MENGGUNAKAN SELEKSI WARNA MODEL HSI PADA CITRA 2D - Didik Hariyanto (Universitas Ahmad Dahlan, 2009)
2D image is a form of image which has coordinates x and y, and override the factors of depth (coordinate z). In an image, there is a color information that consisting of components Red, Green, and Blue (RGB). Color information can be used as a medium for a computer program to interpret objects or values as well as the value of resistor color. By using the color information, a resistor value can be count based on bracelet color. To get good results, RGB color model need to be changed to HSI (hue, saturation, Intensity) color model first. Hue value represent the actual color, saturation level indicates the color saturation, and intensity is used to determine the number of light. By using the color selection based on HSI model and determined the value of threshold, it can be used to express the amount of resistor value in the form of a digital image.